MODALITAS DALAM KONTESTASI POLITIK (Studi kasus kegagalan dr.H. Fahdiansyah, Sp.OG (Ukup) untuk maju dalam Pemilihan Kepala Daerah Kabupaten Kuantan Singingi 2020) - Shertiwan Oktri; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Regional Head Elections in Indonesia in 2020 will be held simultaneously for regions whose term of office for regional heads ends in 2021. Simultaneous Regional Head Election System in 2020 is not the first time but the fourth time it has been held inIndonesia. When the registration process for regional head candidates has been opened at the General Election Commission (KPU) of Kuantan Singingi Regency, until the registration limit for regional head candidates is closed, the Candidate Pair dr. Ukup-Gumpita could not register himself as a candidate for Regent and Deputy Regent of Kuantan Singingi for the 2020-2025 period, this was motivated by the lack of support from political parties from the pair dr. Ukup-Gumpita, as it should be, the absolute requirement to run in the regional head election is to have the support of a political party. This type of research is descriptive qualitative, namely research that intends to describe the phenomena that occur at the research location using the analysis of anatural approach. Data collection techniques include   interviews,  observation,documentation.Based on the results of the research, Modalities in political contestation, apart from the role of candidate figures/modalities, are also largely determined by the role of political and economic support, socio-political and economic actors. In the contestation of the Regional Head General Election, political funds will also determine the winning strategy carried out by the candidate and team. Economic modalities are very much needed to finance all stages of the Regional Head General Election by the candidate and the winning team. And based on the results of the research examined, other causes of dr.ukup's failure to move forward were the lack of planning and strategy in dealing with the PILKADA, lack of support from parties and the problem of dr.ukup's popularity in society. Keywords: Community Participation, in Waste Management.